Metaphorical Disclosure in Jalal Al-Din Rumi's Fihi Ma Fihi - Anisa Hanifah; Dadan Rusmana (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The aim of this research is to elaborate Rumi's metaphorical disclosure in one of his works, entitled Fihi Ma Fihi. The complexity of diction in his literary work can characterize as imagery, specifically as metaphor. Jalal Al-Din Rumi was distinguished by his works containing exquisite language, the unlikeness of his figurative language and imagery, placing him as Persian Poet Top Seller in America in 1997. Therefore, this research utilize the theoretical criticism method in elaborating language and disclosure of Rumi's dialectics in Fihi Ma Fihi. As supporting to approach the analysis, this research also requires library technical and comparative literature methods. The results of this research managed to describe several metaphors that Rumi used as a religious disclosure based on his lectures. Hence, the advantage of this research will be useful for literary devotee in understanding and studying Rumi's writing tactics in influencing the world society for over centuries. This research is also expected to be a basis for further analysis of electing language in literary works production.